Evaluasi Pelaksanaan Tata Letak Gudang Guna Meningkatkan Produktifitas Kerja Pada PT. JNE Logistics - Luthpiyah; Nazif, Fajri (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2026)
The main objective of this study is to evaluate and redesign the layout of goods in warehouses whose efficiency is hampered by the ungrouped placement of products, where the WMS system determines locations based solely on the capacity of empty compartments, resulting in longer placement and retrieval times. This study uses the Class Based Storage method by applying ABC Frequency Classification, grouping goods into fast moving (A), medium moving (B), and slow moving (C), to design a more effective layout. The results show a significant improvement in operational performance, as evidenced by a 28% efficiency in Inbound handling time and a 30% efficiency in Outbound handling time. This reduction in time increased work productivity by 38% for inbound and 45% for outbound. In general, the layout improvement succeeded in speeding up the process and improving performance, but it was concluded that follow-up action was needed in the form of improving the location determination mechanism in the WMS system so that product placement consistently followed the ABC frequency classification and product type grouping.